Animasi Media Pembelajaran Pengenalan Huruf dan Angka Berbasis Android (Studi Kasus : SDN 175740 Aeksiansimun) - Tarigan, Anggi; Tongam E Panggabean; Allwine (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
Currently, the development of information technology makes it easier for teachers and students to access and use learning resources for mastering learning materials or materials. In applying interactive learning media by utilizing audio or voice-based application technology, it is an application that is very useful for reducing boredom, and boredom in terms of learning. The use of this technology application can be done at the elementary school SDN 175740 Aeksiansimun, the ability of students to recognize letters and numbers is still meager, some students don't even understand it at all, tend to get bored and don't pay attention to the explanations of the teaching staff resulting in a decrease in the learning abilities of the school's students. In this study, the learning media that will be produced is an android - based multimedia learning to recognize letters and numbers. The development of the learning system uses the RAD (Rapid Application Development) method in creating an animation system that emphasizes, short and fast development cycles. the results show a good influence on student learning and increase student learning interest.